2005
DOI: 10.3189/172756405781813762
|View full text |Cite
|
Sign up to set email alerts
|

Observations of englacial water passages:a fracture-dominated system

Abstract: To test models of the hydraulics and geometry of englacial conduits, 48 holes (3900m of ice) were drilled into Storglaciaren, Sweden, in search of conduits. About 79% of the holes intersected a hydraulically connected englacial feature. A video camera was used to examine the features and measure local water-flow rates. Because of the extremely clear ice that surrounded most features, their geometry could not be discerned. Of the remaining features, 80% (36) were fracture-like, 16%(6) were of complex geometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In this paper we propose a mechanism for warming induced by englacial water in the ablation zones of glaciers and ice sheets. Englacial water flows through a complex network of crevasses, fractures, moulins (vertical conduits of 10–100 m depth through which melt water drains) and conduits that constitute the CHS [ Fountain and Walder , 1998; Fountain et al , 2005]. The occurrence of water in the CHS during the melt season implies that its temperature is at or above the pressure melting point.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we propose a mechanism for warming induced by englacial water in the ablation zones of glaciers and ice sheets. Englacial water flows through a complex network of crevasses, fractures, moulins (vertical conduits of 10–100 m depth through which melt water drains) and conduits that constitute the CHS [ Fountain and Walder , 1998; Fountain et al , 2005]. The occurrence of water in the CHS during the melt season implies that its temperature is at or above the pressure melting point.…”
Section: Introductionmentioning
confidence: 99%
“…The drilling process itself as well as borehole camera investigation provides additional information on englacial connections (Fountain et al, 2005;Harper et al, 2010). 37 % of all the boreholes drained completely or partially during the drilling process, as did 39 % of those in the cross-glacier lines marked as blue symbols in Fig.…”
Section: Three-dimensional Drainage Structuresmentioning
confidence: 99%
“…Werder et al, 2013), still fail to reproduce direct borehole observations of subglacial conditions . These include the existence of disconnected areas that show no signs of flow-related changes in water pressure (Hodge, 1979;Engelhardt et al, 1978;Murray and Clarke, 1995;Hoffman et al, 2016), the development of widespread areas of high water pressure during winter Harper et al, 2005;Ryser et al, 2014a;Wright et al, 2016), large pressure gradients over short distances (Murray and Clarke, 1995;Iken and Truffer, 1997;Fudge et al, 2008;Andrews et al, 2014), sudden reorganizations of the drainage system (Gordon et al, 1998;Kavanaugh and Clarke, 2000), high spatial heterogeneity, boreholes exhibiting anti-correlated temporal pressure variations (Murray and Clarke, 1995;Gordon et al, 1998;Andrews et al, 2014;Lefeuvre et al, 2015;Ryser et al, 2014a), and englacial conduits (Fountain and Walder, 1998;Nienow et al, 1998b;Gordon et al, 1998;Fountain et al, 2005;Harper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, field studies have shown that these theoretical models of conduit flow may not conform to reality. Boreholes drilled in Storgläciaren, Sweden, predominantly intersect hydraulically connected englacial fracture-like features that are smaller, and with slower water velocities, than traditional conduits, suggesting that englacial water is transported through an interconnected network of fractures rather than large conduits (Fountain et al, 2005). Further field studies are needed to modify theoretical models of englacial drainage.…”
Section: Englacial and Subglacial Drainagementioning
confidence: 96%